2016
DOI: 10.1108/emjb-06-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Does country governance foster revenue efficiency of Islamic and conventional banks in GCC countries?

Abstract: PurposeThe purpose of this paper is to provide new empirical evidence on the impact of country governance on the revenue efficiency of Islamic and conventional banks. The empirical analysis is confined to Islamic and conventional banks operating in the Gulf Cooperation Council (GCC) countries banking sectors during the period of 2007-2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 80 publications
6
73
0
4
Order By: Relevance
“…In assessing efficiency level, Data Envelopment Analysis (DEA) is relatively used more frequently to measure the level of technical efficiency and economies of scale of the banking industry and other financial institutions. Such an analysis is consistent with the research conducted by Rani et al (2017), Kamarudin et al (2016); Ozdemir (2013); Shahreki (2012); and Tsolas and Dimitris (2012), as well as Rusydiana (2018aRusydiana ( , 2018b, Rusydiana & Sanrego (2018), and Rusydiana & Firmansyah (2017).…”
Section: Introduction 11 Backgroundsupporting
confidence: 90%
“…In assessing efficiency level, Data Envelopment Analysis (DEA) is relatively used more frequently to measure the level of technical efficiency and economies of scale of the banking industry and other financial institutions. Such an analysis is consistent with the research conducted by Rani et al (2017), Kamarudin et al (2016); Ozdemir (2013); Shahreki (2012); and Tsolas and Dimitris (2012), as well as Rusydiana (2018aRusydiana ( , 2018b, Rusydiana & Sanrego (2018), and Rusydiana & Firmansyah (2017).…”
Section: Introduction 11 Backgroundsupporting
confidence: 90%
“…Several studies have reported a link between rule of law and entrepreneurship (e.g. Shagbazian & Aistov, 2017;Ngunjiri, 2010;Haggard & Haggard, 2018;Agyemang et al, 2015;Kamarudin et al, 2016;Saona, 2016;Tong et al, 2018;Goltz et al, 2015). The literature review establishes a piece of evidence on the negative effect of regulations (Djankov et al, 2002;Klapper et al, 2006).…”
Section: Rule Of Law and Entrepreneurshipmentioning
confidence: 97%
“…Further, different studies (e.g. Beck, Demirguc-Kunt, Levine, 2006;Kamarudin et al, 2016;Avram et al, 2015;Beck, Demirguc-Kunt & Levine, 2006) agree that transparent and accountable policy is an important determinant for a better business environment and sound economic activity. Guerber and Anand (2019) indicate that corporate governance codes and regulations (e.g.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…In essence, revenue efficiency would be the major factor that influences profit efficiency. Berger and Humphrey (1997), Bader et al (2008) and Kamarudin et al (2016) state that there have been limited studies done on revenue efficiency of banks. Furthermore, if these studies are narrowed down to the Islamic banking industry, there is paucity of studies that looked into the difference in the revenue efficiency of the domestic and foreign Islamic banks.…”
Section: Review Of the Literaturementioning
confidence: 99%